1999
DOI: 10.1046/j.1365-2036.1999.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific inhibition of cyclooxygenase‐2 with MK‐0966 is associated with less gastroduodenal damage than either aspirin or ibuprofen

Abstract: INTRODUCTIONHuman prostaglandin synthesis is catalysed by two isoforms of cyclooxygenase: cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2). 1±4 While COX-1 appears to perform routine physiological functions (such as gastric mucosal protection), 5 COX-2 appears to synthesize prostanoids that mediate responses to pathological processes (such as in¯ammation). It has been suggested that, when compared to the dual inhibition of currently available COX-1/COX-2 inhibitors, the speci®c inhibition of COX-2 is asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(92 citation statements)
references
References 9 publications
5
86
0
1
Order By: Relevance
“…The COX-2 selective NSAIDs (coxibs) were developed to reduce damage to the gastrointestinal mucosa while offering effective analgesia and antiinflammatory action (5). In patients with OA, coxibs have an efficacy similar to nonselective NSAIDs (6), and in patients with OA and rheumatoid arthritis they reduce the risk of peptic ulcer disease and gastrointestinal (GI) bleeding (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The COX-2 selective NSAIDs (coxibs) were developed to reduce damage to the gastrointestinal mucosa while offering effective analgesia and antiinflammatory action (5). In patients with OA, coxibs have an efficacy similar to nonselective NSAIDs (6), and in patients with OA and rheumatoid arthritis they reduce the risk of peptic ulcer disease and gastrointestinal (GI) bleeding (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…and no more than with placebo (Hunt et al, 2000). An endoscopic study in 170 healthy subjects (Lanza et al, 1999) showed that rofecoxib (250 mg/day for 7 days) produced fewer GI mucosal lesions than ibuprofen (2400 mg/day) or aspirin (2600 mg/day) and no more damage than placebo. In two other endoscopic trials lasting 6 months, OA patients receiving rofecoxib (25 or 50 mg/day) manifested a lower incidence of gastroduodenal ulcers than a comparator group treated with ibuprofen (2400 mg/day) (Laine et al, 1999).…”
Section: A Treatment Of Inflammatory Diseasesmentioning
confidence: 99%
“…It has now also been registered in many European countries, Canada, and Australia. In extensive clinical trials, rofecoxib was shown to possess anti-inflammatory and analgesic activity equal to nonselective NSAIDs (Morrison et al, 1999a,b;Cannon et al, 2000;Day et al, 2000) but with much greater GI safety and tolerability (Laine et al, 1999;Langman et al, 1999;Lanza et al, 1999;Hunt et al, 2000;Sigthorsson et al, 2000).…”
Section: A Treatment Of Inflammatory Diseasesmentioning
confidence: 99%
“…Selective COX-2 blockade is an intriguing therapy for symptoms of urinary tract distension and stretch. These medications provide potent analgesia with fewer toxic side effects than nonselective COX inhibitors (Lanza et al, 1999). However, selective COX-2 inhibitors can also be associated with renal side effects, particularly during ureteral obstruction when renal reserve is decreased (Hernandez et al, 2002), and recent reports suggest that high-dose treatment with COX-2 inhibitors is associated with cardiovascular events (Mukherjee et al, 2001).…”
mentioning
confidence: 99%